SWOT Result Analysis For The Sustainable Development Strategy Of Glintung Go Green Wonosari Village, Malang City - Leni Mariani; Wahjoedi; Hadi Sumarsono (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Environmental problems are still a special concern, especially environmental problems that occur in villages within the city, such as problems with garbage, drainage and the absence of green open spaces. Of the various problems faced by Glintung village, Go Green Wonosari can create solutions to overcome these environmental problems. The purpose of this research is to explore the strengths, weaknesses, threats and opportunities, as well as to propose sustainable development strategies in the Glintung Go Green village, Wonosari. This study uses a quantitative type of research with a SWOT analysis approach and the results are carried out. Based on the calculation of the SWOT matrix and the SPACE matrix, the village of Glintung Go Green Wonosari is at the coordinates point (0.78:0.9), this shows that Glintung Go Green is in quadrant one which means it is between strengths and opportunities, the strategy used is the strategy SO. The impact of developing Glintung Go Green Wonosari village through sustainable community empowerment has three aspects, namely, increasing environmental awareness, economic independence and increasing social relations